ANALISIS HUKUM TERHADAP PERLINDUNGAN RAHASIA DAGANG PADA RUMAH MAKAN CHINESE MOEI TJHAN DI KABUPATEN KUBU RAYA KALIMANTAN BARAT - NIM. A1011181264, YOGI HASBIANSARI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This research discusses the legal protection of trade secrets concerning hereditary recipes at Moei Tjhan Restaurant, located in Kubu Raya Regency, West Kalimantan. The background of the study stems from the limited awareness among MSME actors regarding the importance of safeguarding economically valuable commercial information. The research problems include the efforts made by the owner of Moei Tjhan Restaurant to protect its secret recipe and the implementation of employee monitoring mechanisms to maintain such confidentiality. This study employs an empirical juridical method with a descriptive analytical approach. Primary data were collected through in-depth interviews with the owner and eight employees of Moei Tjhan, as well as through field observations of confidentiality procedures. Secondary data were obtained from legal documents such as Law No. 30 of 2000 on Trade Secrets, academic literature, and internal company documents. The data analysis techniques include data reduction, presentation, and qualitative verification. The research findings indicate that Moei Tjhan Restaurant has taken measures to protect its trade secrets by incorporating a Non-Disclosure Agreement clause in its employee contracts. However, negligence occurred when the restaurant failed to draft an employment contract for one employee, relying instead on trust, which ultimately led to the unauthorized use of trade secrets. These findings provide implementable recommendations for other culinary business actors and reinforce the importance of trade secret protection mechanisms within the Micro, Small and Medium Enterprises sector.. Keywords: Hereditary Recipe; Monitoring Mechanism; Trade Secret Protection; Micro, Small and Medium Enterprises Abstrak Penelitian ini membahas perlindungan hukum terhadap rahasia dagang resep turun temurun di Rumah Makan Moei Tjhan, Kabupaten Kubu Raya, Kalimantan Barat. Latar belakang penelitian muncul dari masih minimnya kesadaran pelaku Usaha Mikro Kecil Menengah akan pentingnya upaya menjaga kerahasiaan informasi komersial yang bernilai ekonomi. Rumusan masalah meliputi, upaya apa saja yang dilakukan pemilik Rumah Makan Moei Tjhan dalam melindungi resep rahasianya, dan bagaimana penerapan mekanisme pengawasan terhadap karyawan untuk menjaga kerahasiaan tersebut. Penelitian ini menggunakan metode yuridis-empiris dengan pendekatan deskriptif analisis. Data primer dikumpulkan melalui wawancara mendalam dengan pemilik dan delapan karyawan Moei Tjhan, serta observasi penerapan prosedur kerahasiaan di lapangan. Data sekunder diperoleh dari studi dokumen perundang undangan Undang-Undang Nomor.